Desain Filter Aktif dengan Skema Fuzzy Logic Controller untuk Mereduksi Harmonisa - Irfandi Nu’man Dani; Usman Ba’afai; Marwan Ramli (Universitas Syiah Kuala, 2014)
Harmonics are known as one of the causes of decline in the quality of the electrical power system, which can cause a negative impact on electronic equipment. Harmonics reduction that has been achieved with the passive filters is not quite satisfactory, thus development of active filters is required. This research proposes the use of parallel active filter design using a three-level inverter with the scheme of Fuzzy Logic Controller (FLC) that is used to reduce harmonics. The use of three stages Multilevel Inverter (MLI) on parallel active filter has several advantages that are lowering harmonic distortion and reducing stress switching. From the simulation results, it was obtained that three parallel active filters were capable of reducing the level of harmonic currents and voltages at the source; THDi before installation of the filter was equal to 26,16% and can be lowered to 2,42%. While THDv was reduced from 0,45% to 0,17%. Fifth-order harmonics is the most disturbing harmonic component, in which the value of IHDi beforeinstalling the filter is equal to 21,44% and reduce to 1,2% after the installation of the active filter.